Recommendations for transfusion of blood products in neonatology - Hector Boix; María Dolores Sánchez-Redondo; María Cernada; María Gracia Espinosa Fernández; Noelia González-Pacheco; Ana Martín; Alejandro Pérez-Muñuzuri; María L. Couce (Elsevier, 2022)
The scant evidence on the use of transfusions in neonatal care explains the limitations of current clinical guidelines. Despite this, in this document we explore the most recent evidence to make recommendations for the clinical practice. The prevention of anaemia of prematurity, the use of protocols and restrictive transfusion strategies constitute the best approach for clinicians in this field. In the case of platelet transfusions, the risk of bleeding must be assessed, combining clinical and laboratory features. Lastly, fresh frozen plasma is recommended in neonates with coagulopathy and active bleeding, with congenital factor deficiencies for which there is no specific treatment or with disseminated intravascular coagulation. All blood products have adverse effects that warrant a personalised and thorough assessment of the need for transfusion. Resumen: La escasa evidencia sobre el uso de las transfusiones en neonatología explica las limitaciones de las guías clínicas actuales. A pesar de ello, en este documento analizamos la evidencia más reciente para hacer unas recomendaciones para la práctica clínica. La prevención de la anemia de la prematuridad, el uso de protocolos y las indicaciones restrictivas de transfusión, componen la mejor estrategia para nuestros clínicos. En las transfusiones de plaquetas, es preciso valorar el riesgo de sangrado, integrando la situación clínica y analítica. Por último, el plasma fresco congelado está recomendado en neonatos con coagulopatía y sangrado activo, en déficits congénitos de factores sin tratamiento específico y en situaciones de coagulación intravascular diseminada. Todos los hemoderivados presentan efectos adversos que deben hacernos evaluar individual y minuciosamente la necesidad de una transfusión.